Facile green synthesis of Ag–Cu decorated ZnO nanocomposite for effective removal of toxic organic compounds and an efficient detection of nitrite ions. (15th May 2020) - Manjari, G.; Saran, S.; Radhakrishanan, S.; Rameshkumar, P.; Pandikumar, A.; Devipriya, Suja P.
Abstract: A facile and eco-friendly green synthesis of silver-copper@zinc oxide (Ag–Cu@ZnO) nanocomposite using Acacia caesia flower extract and their application on catalytic reduction of toxic compounds and electrochemical sensing of nitrite ions are reported. The phytochemicals present in the extract were utilized for the Ag–Cu metal nanoparticles synthesis and also enhanced the binding capability between ZnO and Ag–Cu NPs. The synthesized nanocomposites were characterized by XRD, UV–Vis spectroscopy, Raman spectra, FTIR, SEM, TEM, EDX, XPS and ICP-AES for the formation of Ag–Cu NPs on ZnO. The Ag–Cu@ZnO nanocomposite showed better catalytic efficiency as compared to monometallic nanoparticles for 4-nitrophenol to 4-aminophenol conversion and Rhodamine B and Congo red dye degradation with 99% efficiency up to four cycles. The Ag–Cu@ZnO modified GC electrode showed enhanced catalytic activity towards nitrite oxidation, and it exhibited better performance compared to the other nanocomposites. An appreciable detection limit (17 μM) was achieved with excellent sensitivity for nitrite detection. The sensor was highly selective even in a many-fold higher concentration of co-existing interfering compounds. The good catalytic and electrochemical sensing is mainly ascribed due to the synergistic effect of Ag–Cu on the ZnO in the Ag–Cu@ZnO nanocomposite materials. Graphical abstract: Image 1 Highlights: Highly dispersed Ag–Cu@ZnO nanocomposite was synthesized via a greener process. Acacia caesia extract acts as reducing, capping and stabilizing agent for the synthesis of nanoparticles. The Ag–Cu@ZnO showed better electrochemical sensing towards Nitrate ions. The nanocomposites exhibit enhanced performance in the conversion of 4 nitrophenol to 4 aminophenol. The bimetallic nanocomposite shows boosting catalytic activity on organic compounds reduction.